Sintomas do TDAH em crianças e adolescentes: causa ou consequência do ambiente familiar? - Leite, Donizete Tadeu (2017)
Introduction: The approach to Attention-Deﬁcit/Hyperactivity Disorder (ADHD) as a developmental psychopathology has provided predictions of how its symptomatological characteristics can develop over time and how multiple risk factors and protection, including biology and family environment, relate to impact on this development. Objective: Based on this premise, the present study sought to investigate the mutual relationship between some family environmental variables with the intensity of ADHD symptoms in children/adolescents, using a statistical approach to structural equation modeling (SEM). Material and methods: A sample of 111 caregivers of children/adolescents aged from five to 17 years, diagnosed with ADHD, answered the questionnaires about (a) their personality beliefs (PBQ-SF), (b) the quality of family interaction (EQIF), (c) the quality of life of the child/adolescent (PedsQL) and (d) their quality of life perception (WHOQoL-Bref). The relationships between the family environmental variables and these relationships with the intensity of ADHD symptoms in child/adolescent (MTA-SNAP IV) were analyzed, considering two perspectives: ADHD symptoms as predictors of perceived difficulties in the family environment and the family environment as predictor of ADHD symptoms. Results: The results found confirmed the mutual impact between ADHD symptoms in children/ adolescents and family environment factors, especially when they are mediated by negative aspects of family interaction and by a reduced quality of life of the child/ adolescent. Conclusion: The synergism verified between family environmental factors and ADHD symptoms establishes that environmental aspects are considered important predictors for the evaluation of the course and evolution of ADHD symptoms in children/adolescents, as well as the fact that ADHD symptoms may contribute to adversities in the family environment and negatively impact the quality of life. Keywords: Attention-Deficit/Hyperactivity Disorder, personality disorders, family environment, quality of life, child and adolescent, structural equation modeling.